MirTrans: a resource of transcriptional regulation on microRNAs for human cell lines. Issue Volume 46:Issue D1(2018) (25th October 2017) - Hua, Xu; Tang, Rongjun; Xu, Xiuxiu; Wang, Zhi; Xu, Qi; Chen, Luxiao; Wingender, Edgar; Li, Jie; Zhang, Chenyu; Wang, Jin
Abstract: The cell-specific information of transcriptional regulation on microRNAs (miRNAs) is crucial to the precise understanding of gene regulations in various physiological and pathological processes existed in different tissues and cell types. The database, mirTrans, provides comprehensive information about cell-specific transcription of miRNAs including the transcriptional start sites (TSSs) of miRNAs, transcription factor (TF) to miRNA regulations and miRNA promoter sequences. mirTrans also maps the experimental H3K4me3 and DHS (DNase-I hypersensitive site) marks within miRNA promoters and expressed sequence tags (ESTs) within transcribed regions. The current version of database covers 35 259 TSSs and over 2.3 million TF-miRNA regulations for 1513 miRNAs in a total of 54 human cell lines. These cell lines span most of the biological systems, including circulatory system, digestive system and nervous system. Information for both the intragenic miRNAs and intergenic miRNAs is offered. Particularly, the quality of miRNA TSSs and TF-miRNA regulations is evaluated by literature curation. 23 447 TSS records and 2148 TF-miRNA regulations are supported by special experiments as a result of literature curation. EST coverage is also used to evaluate the accuracy of miRNA TSSs. Interface of mirTrans is friendly designed and convenient to make downloads (http://mcube.nju.edu.cn/jwang/lab/soft/mirtrans/ or http://120.27.239.192/mirtrans/ ).